Characterisation of the undrained shear strength of expansive clays at high initial water content using intrinsic concept - Habibbeygi, F.; Nikraz, Hamid (The Geomate International Society, 2018)
© 2018, Int. J. of GEOMATE. Twenty-four direct shear tests were conducted on remolded/reconstituted specimens to study the effect of initial water content on the undrained shear strength of expansive clays. The laboratory tests illustrate that the shear behavior of the studied clayey soil is dependent on both the confining pressure and the initial water content at which the specimen was prepared. In fact, the undrained shear strength decreases with increasing initial water content. Similarly to the compression behavior, the intrinsic concept can also be used to predict the undrained shear strength of the studied soil. Additionally, the relationship between the void index, which is a normalized invariant of void ratio, and the undrained shear strength can be defined uniquely by a straight line. The experimental results also show that the normalized undrained shear strength, which is defined as the ratio of the peak undrained shear strength to the normal stress, varies with the initial water content from 0.25 to 0.50. Moreover, a decreasing trend is found for the range of pre-consolidation stress between 50 and 400 kPa.